Interseeded Native Forbs Resilient Under Variable Grazing Regimen - Jessica L. Prigge; Jonathan D. Richwine; Eric Bisangwa; Patrick D. Keyser (Land)
Reduced floral resources and habitat fragmentation have led to pollinator decline. Increased diversity of native plants in pastures could support cattle and pollinators. However, the relationship between grazing and plant diversity needs to be investigated. We explored how grazing rest periods impacted persistence and forage characteristics of Andropogon gerardii (BB)/Sorghastrum nutans (IG; BBIG) and Panicum virgatum (SG) pastures interseeded with forbs and grazed over five years. ANOVA analysis was conducted using R with significance set at p ≤ 0.05. Forb species exhibited different establishment and flowering characteristics. Coreopsis tinctoria, Rudbeckia hirta (BESU), and Coreopsis lanceolata (LCOR) established early, while Helianthus maximiliani, Heliopsis helianthoides (OSUN), and Echinacea purpurea (PURC) established the second season. Rudbeckia hirta, LCOR, OSUN, and PURC flowered most frequently, and the grazing regimen did not influence the flowering frequency of any species. Desmodium tortuosum (TTFL) was one of the most selected by cattle. Total forage mass declined in 2022, but forb mass interacted with treatment and year where mass declined each year but varied among treatments annually. Based on persistence and forage characteristics, BESU, LCOR, OSUN, PURC, and TTFL could successfully provide forage in native pastures under a variety of grazing regimens.